182k views
4 votes
6 = 2(y + 2)
Solve for Y.

User Vexal
by
6.4k points

2 Answers

3 votes

Answer:

y = 1

Explanation:

6 = 2 (y + 2)

Distribuite:

2 * y = 2y

2 * 2 = 4

2y + 4 = 6

Use additive inverses. The additive inverse of addition is subtraction.

Subtract 4 from both sides:

2y + 4 - 4 = 6 - 4

6 - 4 = 2

2y ÷ 2 = 2 ÷ 2

2y ÷ 2 = y

2 ÷ 2 = 1

To check our answer we multiply how much y is (which is 1) by 2.

2(1) + 4 = 6

2 * 1 = 2

2 + 4 = 6.

User Gary McGowan
by
6.1k points
0 votes

Answer:

6=2(y+2)

distributive property

6=2(y)+2(2)

6=2y+4

-4 -4

2=2y

-- --

2 2

divide two in both sides to get y by itself

y=1

User Franek Madej
by
5.5k points